STRATEGI PEMASARAN KERIPIK PISANG (Musa Paradisca) UNTUK MENINGKATKAN PANGSA PASAR (Market Share) PADA USAHA KECIL DAN MENENGAH (UKM) DI KECAMATAN BATURAJA KABUPATEN OGAN KOMERING ULU (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2017)
Marketing Strategy Analysis Banana Chips (Moses Paradisica) to Increase Market Share in Small and Medium Enterprises (SMEs) in the district of Ulu Ogan Ogan Balfour. This study aimed to analyze the marketing strategy of banana chips to increase market share in Small and Medium Enterprises (SMEs) in the district of Ulu Ogan Ogan Balfour held in May to July 2014. The study was conducted in Ogan Ogan Ulu subdistrict Balfour on some small and medium enterprises (SMEs) are the most widely commercialize banana chips. The method used in this research is purposive sampling method (Accidentally) because in the District Balfour is an industry effort Banana chips highest in Ulu Ogan Ogan. The sampling method used in the study is Simple Random Sampling (Simple Random). Samples are taken as much as 3 samples SME scale upper middle of the most advanced in Ogan Ogan Ulu. The data used are primary data and secondary data. The results showed that banana chips marketing strategy to increase market share in Small and Medium Enterprises (SMEs) in the district of Ulu Ogan Ogan Balfour produce alternative strategy that is best planning strategy that is Expanding network of distributors and channel products to areas that have not been entered. Based on the analysis and calculation of data that small and medium enterprises (SME) that is able to increase market share (market share) amounted to 71.58%, which shows that small and Medium Enterprises in the district of Ulu Ogan Ogan Balfour classified as Market Leader (Leader of Markets) ,